Turkish Fathers’ Language Use In The Context Of Toy Play - Cengiz, Ozge; Cakir, Hamide (European Scientific Journal, ESJ, 2016)
Parent-child interactions and the characteristics of child-directed language have been related to childrenâ€™s linguistic development. Studies on parent-child interactions have generally focused on mothers. There has been very little research on the language used by fathers in interactions with their children. This study addresses this gap by investigating the properties of Turkish paternal language use including their use of question types within the framework of Bloomâ€™s Taxonomy of Cognitive Domain; that is, we try to explore to what extent fathers’ language use differentiates depending on their socioeconomic status in terms of Bloomâ€™s Taxonomy, thus which fathers help their children gain higher thinking skills before entering school. Bloomâ€™s Taxonomy which is a model of classifying thinking according to six cognitive levels of complexity (remember, understand, apply, analyze, evaluate, create) is hierarchical; in that, each level is subsumed by the higher levels. In this cross-sectional study, high and low socioeconomic status (SES) fathers were taped in their homes with their preschoolers in the context of toy play. The results showed that both group of fathers produced the most utterances at the remember level. Both groups produced no utterance at the analyze level, and low SES fathers produced no utterance at the apply and create levels. High SES fathers asked open ended question at all levels except the analyze level, while low SES fathers asked open ended questions only at the remember and understand levels.